Exploring Biotic and Abiotic Determinants of Nest Size in Mediterranean Great Tits (Parus major) and Blue Tits (Cyanistes caeruleus). (12th April 2016) - Lambrechts, Marcel M.; Blondel, Jacques; Bernard, Cyril; Caro, Samuel P.; Charmantier, Anne; Demeyrier, Virginie; Doutrelant, Claire; Dubuc‐Messier, Gabrielle; Fargevieille, Amélie; de Franceschi, Christophe; Giovannini, Pablo; Grégoire, Arnaud; et al.
Abstract: Standardized long‐term multi‐plot investigations of variation in nest size in free‐ranging model species are rare, despite their value for understanding how the environment influences plastic traits such as nest size. Here, we report the results of an 18‐yr descriptive study of nest size in first clutches produced by secondary‐cavity nesting great tits ( Parus major ) and blue tits ( Cyanistes caeruleus ) in the Mediterranean, whilst also taking individual (lay‐date, clutch size, age, species) and environmental characteristics (e.g. weather, oak habitat, region) into account. Nests of both species were built in relatively small standardized boxes erected in habitat patches that differed in the presence of the dominant oak species which was either summergreen deciduous or evergreen sclerophyllous. Nest size showed strong differences between species, and also in relation to environmental factors. Great tits built smaller nests than blue tits, Corsican birds had larger nests than mainland ones, nests tended to be larger in evergreen oak‐habitat, and larger nests were built during drier weather. None of the individual‐specific traits most often considered in long‐term studies (lay‐date, clutch size, and female age) were related to nest size in either species. Experimental approaches will be required to identify the underlying mechanisms that caused the observed phenotypic diversity for nest size in our study system.